2018
DOI: 10.1002/mp.12872
|View full text |Cite
|
Sign up to set email alerts
|

In‐vitro evaluation of accuracy of dynamic contrast‐enhanced ultrasound (DCEUS)‐based parametric perfusion imaging with respiratory motion‐compensation

Abstract: These quantitative results illustrated the disturbances induced by respiratory motion were effectively removed and the accuracy of PPIs was significantly improved. The partial parabolic and bimodal hemodynamic characteristics and the anatomical structures and sizes were accurately quantified and depicted by PPIs with rMoCo. The modified method can benefit physicians in providing accurate diagnoses and in developing appropriate therapeutic strategies for abdominal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 25 publications
(119 reference statements)
0
16
0
Order By: Relevance
“…If diagnostic objects (e.g., liver) were suffered severe distortion during free‐breathing, TIC filtering would be always replaced by the motion compensation and respiratory gating strategies to remove the misregistration of TICs and the distortion of PFIs induced by respiratory motion. Note that the operational efficiencies of above alternative methods for TIC fitting and filtering were also limited by Bessel function‐based correlation estimation, speck tracking, and respiratory phase detection, respectively, which had high computational complexity. However, compared with the hepatic perfusion, the distal end renal perfusion suffered more slight influences induced by respiratory motion, which could be suppressed by the neighborhood smoothing with 3 × 3 pixels in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If diagnostic objects (e.g., liver) were suffered severe distortion during free‐breathing, TIC filtering would be always replaced by the motion compensation and respiratory gating strategies to remove the misregistration of TICs and the distortion of PFIs induced by respiratory motion. Note that the operational efficiencies of above alternative methods for TIC fitting and filtering were also limited by Bessel function‐based correlation estimation, speck tracking, and respiratory phase detection, respectively, which had high computational complexity. However, compared with the hepatic perfusion, the distal end renal perfusion suffered more slight influences induced by respiratory motion, which could be suppressed by the neighborhood smoothing with 3 × 3 pixels in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated the relationship between local hemodynamic characterizations and perfusion parameters, which are proportional to local concentration and perfusion volume of microbubbles, blood flow and rate, respectively . In the past few years, Zhang and Wang et al. applied machine learning and factor analysis algorithms into DCEUS‐based PFI to suppress the disturbances induced by respiratory motion and then enhanced its accuracy and robustness.…”
Section: Introductionmentioning
confidence: 99%
“…The bubble‐echo based PSF built on a multiple microbubble model that considers microbubble interactions and nonlinear propagation as microbubbles will be introduced to BED in our future work. In addition, the improvements of both resolution and CTR in BED also distinctly enhanced the detection sensitivity of microbubbles in CEUS, which has the potential applications in microvascular detection and imaging with low flow . However, the stronger microbubbles attenuation effects with the increasing imaging depth would limit its clinical application in the deeper microvessels .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo abdominal DCEUS-based FPI of a single respiratory phase was reconstructed by considering slight out-of-plane motion 19, 32. 1D perfusion quantification was also corrected under an extreme condition of out-of-plane motion in our previous study 33.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, no study has been conducted on 2D DCEUS-based FPI with serious distortion of angiogenesis under a condition of extreme out-of-plane breathing motion. Out-of-plane motion results in severe image artifacts which inevitably exist in free-breathing hepatic DCEUS studies 19, 32. Under this condition, abovementioned compensation strategies are meaningless and the gating strategies have not been proven to be reliable in the context of DCEUS-based FPI.…”
Section: Introductionmentioning
confidence: 99%